Targeting the KRAS Pathway in Non‐Small Cell Lung Cancer. (2nd November 2016) - Tomasini, Pascale; Walia, Preet; Labbe, Catherine; Jao, Kevin; Leighl, Natasha B.
Abstract : Lung cancer remains the leading cause of cancer‐related deaths worldwide. However, significant progress has been made individualizing therapy based on molecular aberrations (e.g., EGFR, ALK ) and pathologic subtype. KRAS is one of the most frequently mutated genes in non‐small cell lung cancer (NSCLC), found in approximately 30% of lung adenocarcinomas, and is thus an appealing target for new therapies. Although no targeted therapy has yet been approved for the treatment of KRAS ‐mutant NSCLC, there are multiple potential therapeutic approaches. These may include direct inhibition of KRAS protein, inhibition of KRAS regulators, alteration of KRAS membrane localization, and inhibition of effector molecules downstream of mutant KRAS. This article provides an overview of the KRAS pathway in lung cancer and related therapeutic strategies under investigation. Implications for Practice: The identification of oncogene‐addicted cancers and specific inhibitors has revolutionized non‐small cell lung cancer (NSCLC) treatment and outcomes. One of the most commonly mutated genes in adenocarcinoma is KRAS, found in approximately 30% of lung adenocarcinomas, and thus it is an appealing target for new therapies. This review provides an overview of the KRAS pathway and related targeted therapies under investigation in NSCLC. Some of these agents may play a key role in KRAS ‐mutant NSCLC treatment in the future. Abstract : An overview is presented of the KRAS pathway in lung cancer and related therapeutic strategies under investigation. KRAS is one of the most frequently mutated genes in non‐small cell lung cancer (NSCLC). Potential approaches for the treatment of KRAS ‐mutant NSCLC include direct inhibition of KRAS protein, inhibition of KRAS regulators, alteration of KRAS membrane localization, and inhibition of effector molecules downstream of mutant KRAS.